Multimedia security watermarking, steganography, and forensics - Shih, Frank Y. (Taylor & Francis, 2012)
This book provides technical information on multimedia security and steganography as well as the fundamental theoretical framework for developing the extensive advanced techniques. By comprehensively considering the essential principles of the multimedia security and steganographic systems, readers can not only obtain the novel ideas in implementing the advanced algorithms, but also discover the new problems. The book consists of many technical tutorials from various professionals. The text is illustrated with plentiful graphs and examples in order to simplify the problems, so readers can easily understand even complicated theories.